Ferroic Functional Materials Experiment, Modeling and Simulation - Schröder, Jörg.; C. Lupascu, Doru.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
The book covers experiments and theory in the fields of ferroelectrics, ferromagnets, ferroelastics, and multiferroics. Topics include experimental preparation and characterization of magnetoelectric multiferroics, the modeling of ferroelectric and ferromagnetic materials, the formation of ferroic microstructures and their continuum-mechanical modeling, computational homogenization, and the algorithmic treatment in the framework of numerical solution strategies.
Fundamentals of magneto-electro-mechanical couplings: continuum formulations and invariant requirements -- Ferroelectric and ferromagnetic phase field modeling -- Semiconductor effects in ferroelectrics -- Electromechanical models of ferroelectric materials -- An FE2-scheme for magneto-electro-mechanically coupled boundary value problems -- Multiscale modeling of electroactive polymer composites.
Keywords: Materials; Magnetism; Metals; Materials Engineering; Magnetism; Metals and Alloys